2010
DOI: 10.1002/ange.201001197
|View full text |Cite
|
Sign up to set email alerts
|

Eilmeldung: Wolfram spaltet aromatische C‐C‐Bindungen

Abstract: Verblüffende Reaktion: Eine ungespannte, aromatische C‐C‐Bindung in Chinoxalin wird bei der Reaktion mit dem gezeigten (η2‐CH2PMe2)‐Wolframkomplex gespalten, und es bildet sich ein einzigartiger o‐Phenylendiisocyanidkomplex. Der vorgeschlagene Mechanismus verläuft über ein Arin‐Intermediat, das durch doppelte C‐H‐Aktivierung und H2‐Eliminierung entsteht und in dessen C‐C‐Bindung anschließend das Metallatom einschiebt.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…However, as was pointed out by Sattler and Parkin, [14] Goldman, [15] and Walter and Tamm, [16] the validity of the proposed mechanisms needs to be confirmed by means of a computational analysis. Recently, Miscione et al [17] reported an initial theoretical work on this subject.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…However, as was pointed out by Sattler and Parkin, [14] Goldman, [15] and Walter and Tamm, [16] the validity of the proposed mechanisms needs to be confirmed by means of a computational analysis. Recently, Miscione et al [17] reported an initial theoretical work on this subject.…”
Section: Introductionmentioning
confidence: 88%
“…The mechanism of such a process has not yet been determined, which appeals to computational assistance to understand how the unstrained C À C bond is activated at the molecular level. [16,17] In this work, by performing density functional theory calculations, we studied various possible mechanisms of cleavage of the aromatic C À C bond in quinoxaline (QoxH) by the W-based com-…”
Section: Introductionmentioning
confidence: 99%